Board's diversity and the recognition of integrated reports: Are they related? - Braz, M. J. (2019)
This paper investigates the influence of Board of Directors’ diversity on the external reputation of highly Integrated Reports, using a set of international entities. Globalization and competitive environment lead companies to diversify their responsibilities to stakeholders and to the society as a whole. Notwithstanding the need to prepare reports to providers of capital, companies currently must report to a broader audience than shareholders, capturing the attention of several categories of stakeholders. They want to know why, where and how companies create and add value, and how they deal with responsibility and sustainability issues. While an increasingly number of entities are disclosing sustainability and corporate social responsibility (CSR) information, there is still little connection between such information, financial information, performance and value creation strategy. This gap has been over debate, and Integrated Reporting () has emerged. Still voluntary in almost all the world, it is indeed gradually encouraged and supported by regulators, institutional investors and organizations, as an innovative nature in promoting a holistic and integrated vision of the company, where the Board of Directors must play an important role (defining strategies, promoting policies and implementing best practices). The main issue we address is whether different characteristics of Directors seated on the Board impact on the external decision to consider the Integrated Report of that company as a Recognized, instead of a Regular one. Differences between Reference and Regular are supported in the attribution of a premium by external parties, or on the independent recommendation to serve as benchmark. Our sample includes 377 entities all over the world identified as preparers, from whom people expect to be accountable for the transparency of their external communication process. Main findings reveal that while the role duality of the CEO has a negative influence, the board size, the independence of the board and the gender diversity are positively contributing to the diffusion of integrated reports of higher recognition, and Experience is not statistical significant. The results are maintained when institutional characteristics of the countries are included.